"المقدّر الحصين لنموذج تجميعي معمّم شبه معلمي" - رشيد ظافر حسين; علي عمر عبد المحسن (Journal of Economics and Administrative Sciences, 2008)
Generalized Additive Model has been considered as a multivariate smoother that appeared recently in Nonparametric Regression Analysis. Thus, this research is devoted to study the mixed situation, i.e. for the phenomena that changes its behaviour from linear ( with known functional form) represented in parametric part, to nonlinear (with unknown functional form: here, smoothing spline) represented in nonparametric part of the model. Furthermore, we propose robust semiparametric GAM estimator, which compared with two other existed techniques.